Extension of Cellular Lifespan by Methionine Restriction Involves Alterations in Central Carbon Metabolism and Is Mitophagy-Dependent - Plummer, Jason D.; Johnson, Jay E. (Frontiers in Cell and Developmental Biology, 2019)
Methionine restriction (MR) is one of only a few dietary manipulations known to robustly extend healthspan in mammals. For example, rodents fed a methionine-restricted diet are up to 45% longer-lived than control-fed animals. Tantalizingly, ongoing studies suggest that humans could enjoy similar benefits from this intervention. While the benefits of MR are likely due, at least in part, to improved cellular stress tolerance, it remains to be determined exactly how MR extends organismal healthspan. In previous work, we made use of the yeast chronological lifespan (CLS) assay to model the extension of cellular lifespan conferred by MR and explore the genetic requirements for this extension. In these studies, we demonstrated that both dietary MR and genetic MR (i.e., impairment of the cell’s methionine biosynthetic machinery) significantly extend the chronological lifespan of yeast. This extension was found to require the mitochondria-to-nucleus retrograde stress signaling pathway (RTG), and was associated with a multitude of gene expression changes, a significant proportion of which were also dependent on RTG signaling. Here, we show work aimed at understanding how a subset of the observed expression changes are causally related to MR-dependent CLS extension. Specifically, we find that multiple autophagy-related genes are upregulated by MR, likely resulting in an increased autophagic capacity. Consistent with activated autophagy being important for the benefits of MR, we also find that loss of any of several core autophagy factors abrogates the extended CLS observed for methionine-restricted cells. In addition, epistasis analyses provide further evidence that autophagy activation underlies the benefits of MR to yeast. Strikingly, of the many types of selective autophagy known, our data clearly demonstrate that MR-mediated CLS extension requires only the autophagic recycling of mitochondria (i.e., mitophagy). Indeed, we find that functional mitochondria are required for the full benefit of MR to CLS. Finally, we observe substantial alterations in carbon metabolism for cells undergoing MR, and provide evidence that such changes are directly responsible for the extended lifespan of methionine-restricted yeast. In total, our data indicate that MR produces changes in carbon metabolism that, together with the oxidative metabolism of mitochondria, result in extended cellular lifespan.